PERSEPSI PESERTA DIDIK KELAS XII TENTANG PENDIDIKAN SEKS DI SMA NEGERI 1 NAN SABARIS - Susanti, Endang; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
Based on problem studied that researcher found from the phenomenon that researcher seen in the field was limited given of information about sex and the manner in which the righ to adolescents by counceling. Besed on the phenomenonthat the researchers raised concerns abuot : 1) Persepsion of students about sex education materials 2) Persepsion of students about sex education methods 3) Persepsion of students about implemeting sex education 4) Persepsion of students about the importance of sex education. This researched was quantitative deskriptive research that seeks to describe the situation for what it is. The study populations were all students of class XII are numbered 258. The technique used in this sampling was simple random sampling the sample taken was class XII and XII IS 2 IA 3, amounting to 59 people. The instrument used in this study was a questionnaire. As for the use of data analysis is techniques percentage. The researched resultsrevealed that : 1) Perception of students about sex education materials were classified as good 2) Perception of students about sex education methods were classified as good 3) Perception of students about sex education executive was fair 4) Perception of students about the importance of education peseta sex was good.